2006
DOI: 10.1182/blood-2005-08-3503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transgene-specific immune responses that limit the in vivo persistence of adoptively transferred HSV-TK–modified donor T cells after allogeneic hematopoietic cell transplantation

Abstract: IntroductionThe genetic modification of cells has the potential to improve upon current therapies for inherited and acquired diseases. For example, the introduction of a conditional suicide gene into T cells has been proposed as a strategy for enhancing the safety of adoptive T-cell therapy for cancer where the antigens targeted by transferred T cells are expressed on both normal and malignant cells [1][2][3][4][5][6] or where T cells are modified to confer novel functions that might improve antitumor efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
251
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(254 citation statements)
references
References 56 publications
2
251
1
Order By: Relevance
“…Furthermore, immunogenicity of the gene-modified cells is likely to be minimal, because of the lack of substantial amounts of nonhuman sequence. This offers a substantial advantage over the HSV-TK system, where the survival of gene-modified cells may be limited due the immunogenicity of the HSV-TK gene product (11), and where ganciclovir treatment of CMV infection can also lead to the untimely elimination of the infused cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, immunogenicity of the gene-modified cells is likely to be minimal, because of the lack of substantial amounts of nonhuman sequence. This offers a substantial advantage over the HSV-TK system, where the survival of gene-modified cells may be limited due the immunogenicity of the HSV-TK gene product (11), and where ganciclovir treatment of CMV infection can also lead to the untimely elimination of the infused cell population.…”
Section: Discussionmentioning
confidence: 99%
“…However, ganciclovir is also frequently used to treat CMV infections in patients who undergo allogeneic stem cell transplantation (allo-SCT), resulting in an unwanted elimination of the genetically modified cells. More importantly, unwanted elimination of the transferred T cells as a consequence of immune responses toward the HSV-TK gene product has been observed in a substantial fraction of patients, likely limiting the use of this safety switch to patients who are immune suppressed at the time of T cell infusion (11,12). As a first possible nonimmunogenic alternative safety switch, a human CD20 molecule has been validated in preclinical studies (13,14).…”
mentioning
confidence: 99%
“…First, the HSV-TK enzyme used in initial clinical efforts is highly immunogenic, thereby likely limiting the in vivo persistence and immune therapeutic efficacy of transgene-expressing T cells. 13,30 In a second approach, T cell expression of iCasp9 allowed dimerization of proapoptotic molecules thus resulting in rapid elimination of transgene-expressing T cells and subsequent reduction in GVHD; 15 however, the dimerizing agent prodrug is not FDA inhibits cytokine signaling and the cell cycle machinery required for T cell proliferation 35,36 one might hypothesize that T cells treated in vitro with rapamycin would be refractory to LV transduction. That is, LV is known for transducing many types of nondividing cells and also for promoting stable gene expression, but one limitation is its relative inability to infect resting T cells; 37 consistent with this point, in previous studies, T cell transduction in the setting of increased IL2 signaling was permissive for LV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide genes may be incorporated into CAR-encoding vectors. Thymidine kinase from HSV (HSV-TK) has been used as an effective suicide gene in transferred T cells, but its immunogenicity may limit its future utility in adoptive T cell transfer [58,63]. Recent studies demonstrated that administration of a small molecule dimerizer (AP1903) to allogeneic HCT recipients induced rapid amelioration of acute GVHD and elimination of transplanted T cells that were engineered to express an AP1903-inducible caspase [64].…”
Section: Strategies To Improve the Safety Of Car-modified T Cellsmentioning
confidence: 99%